A multidisciplinary protocol for reducing excessive and maintaining a healthy body weight in the personalized management of chronic diseases in children and adults - Ivana Banić; Marija Jankić; Adrijana Miletić Gospić; Katarina Pentek; Petra Anić; Tajana Burkuš; Krešimir Hrg; Karmen Zadro; Jelena Miličević; Ivana Šuljić; Marcel Lipej; Davor Plavec; et al. (PLoS ONE, 2025)
Despite regularly used treatment asthma in both children and adults is not fully controlled. This is more prominent in certain disease subtypes, such as obese asthma. The vast complexity of asthma phenotypes and often overlapping endotypes emphasizes the need for implementing the concept of precision medicine in disease management. In order to address these concerns, an innovative and personalized programme for reducing excessive and maintaining a healthy body weight will be developed by experts from pharmaceutical and food industry (Belupo Inc. and Podravka Inc., Croatia) as well as clinical experts (Srebrnjak Children`s Hospital, Croatia). The programme will involve meals replacement (standard and innovative formulas), dietary program and nutritional counseling, physical activity and other individually tailored measures according specific disease phenotypes and underlying pathophysiological mechanisms in each participant. The outcomes of this study should contribute to better control of the underlying condition, reduction of the frequency and severity of symptoms and, consequently, in the improvement of the participant’s overall quality of life.